Socialization experiences of physical culture vs. life style in old age - Koszczyc, Marta; Łupicka-Szczęśnik, Dagmara (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
In the literature representing physical culture a discourse is taking place concerning the problems of socialization in the family as the primary transmitter of physical activity patterns to prepare young generations for conscious participation in physical culture. In empirical studies there is a gap pertaining to the identification of problems of recreational and sports experiences acquired in childhood and cultural activity undertaken by humans in relation to physical exercise in old age. Therefore, the objective of the study was to determine the cause and effect relationship between family socialization (the internalization of physical culture patterns and standards) and the lifestyle in old age.
Keywords: family; physical education; corporeal habitus; lifestyle